CONTEMPORARY TENDENCIES IN TEACHING LITERACY THE PRIMARY SCHOOL: CONTEMPORARY TENDENCIES IN TEACHING LITERACY THE PRIMARY SCHOOL - Yordanova , Daniela (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The article reviews some of the contemporary tendencies in the teaching of basic literacy to primary-school pupils – the goal and the tasks of the education process; the accents in the analythical-synthetic method of teaching literacy in the primary school in Bulgaria; the didactic tools to guarantee a quality basic-literacy teaching for the children from minority communities in connection with the renewal of our education system, which forms part of the European one.